2011
DOI: 10.4103/0976-7800.92529
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione peroxidase activity in obese and nonobese diabetic patients and role of hyperglycemia in oxidative stress

Abstract: Background:Both hyperglycemia and obesity are known to cause oxidative stress, which leads to many complications associated with diabetes mellitus. A large number of diabetic patients are obese. Glutathione peroxidase (GPx) is an important indicator of level of oxidative stress.Materials and Methods:In the present study, we assessed GPx levels in 20 healthy controls, obese, and nonobese diabetic patients (n=20 each) and analyzed the effect of insulin treatment for 24 and 48 weeks on GPx activity. GPx activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…Nevertheless, we found no difference in GPx activity between T2DM, pre-DM and control groups. As for SOD, data regarding GPx activity in T2DM are also controversial: Plasma and intracellular GPx levels have been shown to be decreased [22, 23] or unchanged [16] in T2DM patients compared to healthy controls. Increased SOD activity unaccompanied by an increase in GPx could lead to increased H 2 O 2 levels that could be deleterious, but measuring this is masked because of the apparent blood volume and the natural reactivity of H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we found no difference in GPx activity between T2DM, pre-DM and control groups. As for SOD, data regarding GPx activity in T2DM are also controversial: Plasma and intracellular GPx levels have been shown to be decreased [22, 23] or unchanged [16] in T2DM patients compared to healthy controls. Increased SOD activity unaccompanied by an increase in GPx could lead to increased H 2 O 2 levels that could be deleterious, but measuring this is masked because of the apparent blood volume and the natural reactivity of H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Superoxide is converted to the H 2 O 2 by SOD to oxygen and water by antioxidant enzymes such catalase and GPx. Goyal et al [ 25 ] reported lower activity of GPx in obese diabetic patients and Kornhauser et al [ 26 ] showed in first-degree relatives of patients of T2DM an over expressing of GPx gene as defense mechanisms to protect cell from oxidative stress [ 27 ]. Conversely, our results have shown that activity of GPx was not found different between IR group and without IR group in first-degree relatives T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…An imbalance between the production of reactive oxygen species (ROS) and intracellular antioxidant capacity underlies the development of oxidative injury which forms the basis for the development of many pathologic conditions [ 47 ]. A decrease or an increase in the activities of enzymatic antioxidant proteins (manganese superoxide dismutase (MnSOD) and GPx) has consistently been noted during oxidative stress [ 48 , 49 ]. An unchecked increase in ROS within the cell eventually results in lipid peroxidation, oxidative protein and nucleic acid damage [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%